Illocutionary Strategies in Digital Advertisement Campaign as Found in Coca-Cola’s #Makeithappy - Dhenok Wulandari (Lexicon, 2015)
Language used in a campaign is an interesting study, moreover if it is used in a campaign which targets adolescent audience who are known with their own dynamics. The study uses the sample of advertisement campaign from The Coca-Cola Company entitled #MakeItHappy which aims to fight the increasing online bullying in the digital era nowadays, especially to American's adolescents. The data are taken from five videos containing thoughts and testimonials from celebrities, experts, and some adolescents who experience and/or having a concern with the issue. The language used there is identified by Austin's illocutionary speech acts then analyzed by the theory of Searle. The study shows that the type of speech act which is seen in high frequency is assertive-directive indirect speech (66,7%). This result implies that assertive-indirect directive indirect strategy is the most appropriate strategy to be used towards teenagers in the context of advertisement campaign.